0409 How Does Intensive Sleep Retraining (ISR) Compare to CBT-I?. (27th April 2018) - Boyle, J T; Muench, A; Gencarelli, A; Khader, W; Perlis, M L
Abstract: Introduction: Intensive Sleep Retraining (ISR) is a brief in-laboratory therapy for chronic insomnia. The procedure utilizes sleep deprivation in combination with repeated sleep onset opportunities to promote "sleep ability" and counter-conditioning. In preparation for an independent study of ISR, prior ISR studies were evaluated and compared to meta-analytic data to address how ISR compares to CBT-I in terms of acute outcomes (relative efficacy). Methods: Published ISR data was identified via PubMed. Effect sizes were calculated based on change from pre-treatment to end-of-treatment. These data were compared to two CBT-I meta-analyses, one recent and comprehensive (2010) and one well-established and highly cited (2002). For the 2010 study, the effect sizes were recalculated to represent unadjusted pre-post values. Results: The Sleep Latency (SL) effect sizes for the two ISR studies were 1.08 for both the 2007 and 2012 trials. The two reference meta-analyses SL values were 1.01 (2002) and 1.40 (2010). The Wake After Sleep Onset (WASO) effect sizes for the ISR studies were 0.28 (2007) and 0.46 (2012). The two reference meta-analyses WASO values were 1.16 (2002) and 1.98 (2010). Conclusion: This evaluation suggests that ISR and CBT-I have comparable acute effects on sleep initiation problems, with the more recent meta-analysis suggesting that CBT-I produces slightly larger effects for SL. As suggested by the treatment innovators, ISR is primarily indicated for sleep initiation problems and this is borne out by the data here, which suggests that CBT-I is superior to ISR for sleep maintenance issues. While future studies will need to independently assess the efficacy of ISR (and its durability), the data available suggests that lab-based ISR may constitute another level for stepped care. This may be particular true for CBT-I subjects that are non-responders to CBT-I owing to non-adherence. Support (If Any): Support for a pilot test of ISR is being provided by the Penn Center for Sleep and Circadian Neurobiology and the Marpac Corporation.